Micro-nano-scale ceramic particle reinforced high-chromium cast iron-based composite material as well as preparation method and application thereof
By pickling, sensitizing and plating the ZTA ceramic particles, combined with ball milling and discharge plasma sintering technology, ceramic particle-enhanced high-chromium cast iron matrix composite materials were prepared, solving the interface failure problem of ceramic particles in the iron matrix, significantly Improves the wear resistance and hardness of the material.
Patent Information
- Application Number
- CN202411051285.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-01
- Publication Date
- 2024-12-24
AI Technical Summary
Existing ceramic particle-reinforced iron-based composites are prone to failure at the interface when high stress wear, resulting in insufficient wear resistance and difficulty in preparing the uniform distribution of micro-nano-scale ceramic phases in the iron matrix.
Micron ZTA ceramic particles were pickled, sensitized and activated by SnCl2 and PdCl2, and NiMo metal plating was deposited, and micro-nanoscale ceramic particles were prepared through ball milling and discharge plasma sintering technology to form dense Coating and evenly distributed VC ceramic particles.
It significantly improves the hardness, strength and wear resistance of the material, reduces the wear amount of the matrix material, realizes the positioning and recombination of the micro-nanoscale ceramic phase in the iron matrix, and breaks the market monopoly of high-performance wear-resistant components.
Smart Images

Figure CN119177391A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of wear-resistant material preparation, and specifically relates to a micro-nanoscale ceramic particle reinforced high-chromium cast iron-based composite material and a preparation method and application thereof. Background Art
[0002] Wear-resistant materials, as important consumable materials in the equipment manufacturing industry, are important basic materials for the operation of the national economy and national safety production. They are widely used in key moving parts of heavy machinery equipment in industrial sectors such as mining, metallurgy, electricity, machinery, building materials, automobiles, trains, military industry, and aerospace, such as automobile engine cylinder liners, pistons, brake drums and brake discs; train bogies and brake discs; large crusher crushing walls, plate hammers (hammers); large vertical mill grinding rollers, grinding discs, linings, etc. Steel materials have an irreplaceable position in the field of wear-resistant materials due to their advantages such as low cost and high hardness, but they still have problems such as low strength, poor corrosion resistance, and insufficient wear resistance. Introducing a high content of the second strengthening phase into the steel matrix can significantly improve the strength and wear resistance of the material. Oxide ceramics have excellent corrosion resistance and can slow down the corrosion rate of the matrix, thereby extending its service life. However, the high-temperature wetting angle between oxide ceramics and iron matrix is large, resulting in mechanical bonding at the interface, which leads to preferential failure at the interface during high-stress wear. High-melting-point transition metals can improve the wettability of oxide ceramics and iron matrix, so coating the surface of ceramic particles with transition metal coatings can improve the bonding strength of the heterogeneous interface of the composite material. Since the hardness of the iron matrix is significantly lower than that of the oxide particles, the matrix is removed first during the wear process, causing the ceramic particles to protrude significantly from the wear surface, and even causing the ceramic particles to peel off as a whole. Therefore, the introduction of nano-VC ceramics around micron ceramic particles can further improve the hardness and strength of the matrix, while Mo reacts with carbon to generate a large amount of primary carbides, ensuring the service stability and safety of the composite material, breaking the market monopoly and technical blockade of foreign companies on high-performance wear-resistant parts. Summary of the invention
[0003] The technical problem to be solved by the present invention is to provide a micro-nanoscale ceramic particle reinforced high chromium cast iron-based composite material and its preparation method and application in view of the deficiencies in the above-mentioned prior art, so as to solve the technical problem that dual-phase cross-scale ceramic particle reinforced iron-based composite materials are difficult to prepare. The prepared iron-based composite material with synergistic reinforcement of micro-nanoscale ceramic phases has high strength, high toughness and high wear resistance, realizes the positioning composite of micro-nanoscale ceramic phases in the iron matrix, and significantly reduces the wear of the matrix material.
[0004] The present invention adopts the following technical solutions:
[0005] A method for preparing a micro-nanoscale ceramic particle reinforced high-chromium cast iron-based composite material comprises the following steps:
[0006] The micron ZTA ceramic particles were pickled, sensitized and activated by SnCl2 and PdCl2 respectively.
[0007] A continuous and dense NiMo metal coating is deposited on the surface of ZTA ceramic particles to obtain NiMo@ZTA;
[0008] The NiMo@ZTA, V powder, high chromium cast iron powder and alcohol are ball-milled and mixed, so that the V powder and high chromium cast iron powder are evenly coated on the surface of ZTA, and then dried, crushed and sieved in sequence;
[0009] Under pressure, micro-nanoscale ceramic particle reinforced high chromium cast iron matrix composites were prepared by spark plasma sintering technology.
[0010] Preferably, the pickling treatment is specifically:
[0011] The ZTA ceramic particles of 50-200 μm were soaked in acetone for 10-15 h, then rinsed with deionized water, and then acid-washed with a mixed solution of 50-150 ml / L H2SO4 and 100-200 g / L (NH4)2SO4 at room temperature;
[0012] The specific sensitization treatment is:
[0013] The pickled ZTA ceramic particles are sensitized in a 10-50 g / L SnCl2 and 30-80 ml / L hydrochloric acid solution for 10-30 min;
[0014] The activation treatment is as follows:
[0015] The ZTA ceramic particles were rinsed with deionized water until the pH value was 7, and then activated by 0.1-0.5 g / L PdCl2 and 10-20 ml / L HCl solution for 10-30 min.
[0016] Preferably, after the activation treatment, the mixture is washed with deionized water until it becomes neutral; and 10 to 30 g / L of NaH2PO2·H2O is used to remove excess Pd ions.
[0017] Preferably, depositing a continuous and dense NiMo metal coating on the surface of the ZTA ceramic particles is specifically as follows:
[0018] Every 50-100g of ZTA ceramic particles are magnetically stirred with 200-300ml of plating solution, the pH value of the plating solution is 9-11, and the plating temperature is maintained at 60-80°C by water bath heating, and the plating solution is replaced every 60-120min.
[0019] Preferably, the plating solution is specifically:
[0020] The main salt is a mixed solution of 10-20 g / L NiSO4·6H2O and 1-5 g / L Na2MoO4·2H2O, the reducing agent is 15-25 g / L NaH2PO2·H2O, the complexing agent is 10-20 g / L CH3COONa, and the pH value of the plating solution is adjusted with ammonia water.
[0021] Preferably, NiMo@ZTA, V powder, high chromium cast iron powder and alcohol are ball-milled and mixed, and then dried, crushed and sifted in sequence. The specific steps are as follows:
[0022] 10-30wt.% ZTA ceramic particles coated with NiMo coating, 1-3mL / g alcohol, 1-5wt.% V powder and high chromium cast iron powder are ball-milled, the ball-ink tank and grinding balls are both made of stainless steel, the ball-to-material ratio is 5:1-10:1, the ball-milling time is 5-10h, the number of revolutions is 100-300rpm, and then vacuum dried and sieved.
[0023] Preferably, the micro-nanoscale ceramic particle reinforced high chromium cast iron-based composite material prepared by spark plasma sintering technology is specifically:
[0024] The sintering temperature was controlled to be 900-1200°C, the heating rate from room temperature to 600°C was 100°C / min, the heating rate from 600°C to sintering temperature was 50°C / min, the holding time was 10-20min, and the vacuum degree was 2-8×10 -6 Pa, the power supply voltage is 300-500V, the DC voltage is 3-4V, the dispersed V powder reacts with the carbon in the matrix in situ to generate VC ceramic particles, which are cooled with the furnace.
[0025] Preferably, the pressure of the upper and lower pressure heads is 30-40 MPa.
[0026] Another technical solution of the present invention is a micro-nanoscale ceramic particle reinforced high-chromium cast iron-based composite material.
[0027] Another technical solution of the present invention is that the micro-nanoscale ceramic particle reinforced high-chromium cast iron-based composite material is applied to wear-resistant parts.
[0028] Compared with the prior art, the present invention has at least the following beneficial effects:
[0029] A method for preparing a micro-nanoscale ceramic particle-reinforced high-chromium cast iron-based composite material, in order to meet the sustainable industrial development needs such as low energy consumption, high efficiency, and environmental friendliness, the surface of ZTA ceramic particles is metallized by chemical plating. The wettability of transition metal NiMo and ZTA ceramics is poor, Ni can be fully dissolved in the iron matrix, Mo has excellent antioxidant properties, and Mo reacts with Al2O3 at high temperature to form a ternary oxide, which can improve the interface bonding strength between ZTA ceramic particles and the iron matrix. The present invention adopts spark plasma sintering technology to prepare a multi-scale ceramic particle-reinforced iron-based composite material, reduces the sintering temperature of the composite material and shortens the sintering time through pressure-assisted action, and the V powder uniformly distributed around the ZTA ceramic particles reacts in situ with the carbon in the high-chromium cast iron to synthesize fine VC ceramic particles, which hinders dislocation movement. Therefore, the strength and wear resistance of the high-chromium cast iron matrix are further improved under the premise of ensuring the high hardness of the micron ZTA particles.
[0030] Furthermore, the surface adhesion and surface roughness of micron-sized ZTA ceramic particles were improved through acetone, acid washing, sensitization and activation treatments.
[0031] Furthermore, chemical plating has the advantages of simple process, high deposition efficiency, uniform coating composition, strong bonding between the coating and the ceramic substrate, and low cost.
[0032] Furthermore, wet mixing during ball milling can effectively prevent oxidation of the powder, and the use of stainless steel grinding balls and ball mill jars can avoid the introduction of other impurities into the mixed powder.
[0033] Furthermore, in order to facilitate demoulding of the composite material from the mold after sintering, a layer of boron nitride powder is sprayed on the inside of the graphite mold and the outside of the pressure head, and the mixed powder is separated from the graphite mold with graphite paper to prevent the iron powder from reacting with graphite and sticking to it.
[0034] Furthermore, the combination of high-energy ball milling and spark plasma sintering can make the micron-sized ZTA ceramic particles evenly distributed in the high-chromium cast iron matrix, and the VC particles obtained by in-situ reaction have excellent interface bonding properties with the matrix.
[0035] Furthermore, in the process of preparing composite materials by powder metallurgy, there is no need to introduce binders such as silicates, and there is no need to sinter the ceramic particle preform at high temperature in advance.
[0036] In summary, the present invention deposits a metal coating on the surface of ZTA ceramic particles by chemical plating to form a core-shell structure on the surface of the ceramic particles, adopts a wet mixing method to evenly mix the metallized ZTA ceramic particles, V powder and high chromium cast iron powder, and sinters the mixed powder under pressure by a spark plasma sintering method to form a ceramic particle reinforced iron-based composite material with a uniform distribution of a reinforcement phase, and in situ synthesizes VC particles with the V powder and carbon in the matrix, which significantly improves the hardness and wear resistance of the matrix, thereby obtaining a micro-nanoscale ceramic particle reinforced iron-based composite material.
[0037] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 This is a photo of the composite material prepared in Example 1 of the present invention;
[0039] Figure 2 This is the interface morphology between the ZTA ceramic particles and the matrix of the composite material in Example 1 of the present invention. DETAILED DESCRIPTION
[0040] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0041] In the present invention, unless otherwise specified, all the embodiments and preferred implementation methods mentioned herein can be combined with each other to form a new technical solution.
[0042] In the present invention, unless otherwise specified, all technical features and preferred features mentioned herein can be combined with each other to form a new technical solution.
[0043] In the present invention, unless otherwise specified, percentage (%) or part refers to the weight percentage or weight part relative to the composition.
[0044] In the present invention, unless otherwise specified, the components or preferred components involved can be combined with each other to form a new technical solution.
[0045] In the present invention, unless otherwise specified, the numerical range "a-b" represents an abbreviation of any real number combination between a and b, where a and b are real numbers. For example, the numerical range "6-22" means that all real numbers between "6-22" have been listed in this document, and "6-22" is just an abbreviation of these numerical combinations.
[0046] The “range” disclosed in the present invention is in the form of a lower limit and an upper limit, which can be one or more lower limits, and one or more upper limits, respectively.
[0047] In the present invention, the term "and / or" used herein refers to any combination and all possible combinations of one or more of the associated listed items, and includes these combinations.
[0048] In the present invention, unless otherwise specified, each reaction or operation step can be carried out sequentially or in accordance with the sequence. Preferably, the reaction method herein is carried out sequentially.
[0049] Unless otherwise specified, the professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any method or material similar or equivalent to the described content may also be applied to the present invention.
[0050] The invention provides a micro-nanoscale ceramic particle reinforced high-chromium cast iron-based composite material and a preparation method and application thereof. Micron ZTA ceramic particles are pickled, sensitized and activated with SnCl2 and PdCl2 respectively, and then a NiMo metal coating is chemically plated on the ZTA ceramic particles with the aid of a magnetic stirrer, wherein the plating solution is alkaline, and then NiMo@ZTA, V powder, high-chromium cast iron powder and alcohol are uniformly mixed on a ball mill, and then injected into a graphite mold; under the action of pressure, the composite material is prepared by a spark plasma sintering technology, and the dispersed V reacts in situ with the carbon in the matrix to generate nano VC ceramic particles; the micron ZTA ceramic particles provide excellent wear resistance, and the nano VC ceramics increase the strength and hardness of the matrix, thereby obtaining a micro-nanoscale ceramic particle reinforced iron-based composite material.
[0051] The present invention discloses a method for preparing a micro-nanoscale ceramic particle reinforced high-chromium cast iron-based composite material, comprising the following steps:
[0052] S1. Soak 50-200 μm ZTA ceramic particles in acetone for 10-15 h, then rinse with deionized water, and then pickle the ZTA ceramic particles with a mixed solution of 50-150 ml / L H2SO4 and 100-200 g / L (NH4)2SO4 at room temperature;
[0053] S2, sensitizing the acid-washed ZTA ceramic particles in 10-50 g / L SnCl2 and 30-80 ml / L hydrochloric acid solution for 10-30 min; rinsing the ZTA ceramic particles with deionized water until the pH value is 7, then activating them with 0.1-0.5 g / L PdCl2 and 10-20 ml / L HCl solution for 10-30 min, and then washing them with deionized water until they are neutral; removing excess Pd ions with 10-30 g / L NaH2PO2·H2O;
[0054] The micro-meter-sized ZTA ceramic particles were successively treated with acetone cleaning, acid washing, sensitization and activation to improve the surface activity of the ZTA ceramic particles.
[0055] S3, depositing a transition metal NiMo coating on the surface of the activated ZTA ceramic particles by chemical plating, using 200-300 ml of plating solution for every 50-100 g of ZTA ceramic particles, plating on a magnetic stirrer, the main salt is a mixed solution of 10-20 g / L NiSO4·6H2O and 1-5 g / L Na2MoO4·2H2O, using 15-25 g / L NaH2PO2·H2O as a reducing agent, and a complexing agent of 10-20 g / L CH3COONa, adjusting the pH value of the plating solution to 9-11 with ammonia water, heating in a water bath, maintaining the plating temperature at 60-80°C, and replacing the plating solution every 60-120 min;
[0056] The magnetic stirrer assists in chemically plating the NiMo coating on the surface of the micron ZTA ceramic particles. The rotor in the reaction vessel rotates to make the plating solution flow, allowing the plating solution to fully contact the fine ZTA ceramic particles. In order to obtain a dense metal coating on the surface of the ZTA ceramic particles, an alkaline plating solution is selected.
[0057] S4, grinding 10-30wt.% ZTA ceramic particles coated with NiMo coating, 1-3mL / g alcohol, 1-5wt.% V powder and high chromium cast iron powder in a high energy ball mill to make the V powder, high chromium cast iron powder and ZTA ceramic particles evenly mixed, the ball mill and grinding balls are made of stainless steel, the ball-to-material ratio is 5:1-10:1, the ball milling time is 5-10h, the number of revolutions is 100-300rpm, and the moisture is removed in a vacuum drying oven and sieved;
[0058] The metallized ZTA ceramic particles, nano V powder and high chromium cast iron powder are evenly mixed by ball milling using a high-energy ball mill, and the V powder and high chromium cast iron powder are evenly coated on the surface of the ZTA ceramic particles. During the ball milling process, alcohol is used as a medium to reduce the pressure and temperature of the ball mill and prevent the metal powder from being oxidized.
[0059] S5, inject the mixed powder into a Φ40×120mm graphite mold, and prepare the composite material by spark plasma sintering, the upper and lower pressure head pressure is 30-40MPa, the sintering temperature is 900-1200℃, the heating rate from room temperature to 600℃ is 100℃ / min, the heating rate from 600℃ to sintering temperature is 50℃ / min, the holding time is 10-20min, and the vacuum degree is 2-8×10 -6Pa, the power supply voltage is 300-500V, the DC voltage is 3-4V, the dispersed V powder reacts with the carbon in the matrix in situ to generate VC ceramic particles, which are cooled in the furnace to obtain a multi-scale ceramic reinforced iron-based composite material.
[0060] The dried mixed powder is slowly poured into the graphite mold, and the spark plasma sintering technology is used to prepare the micro-nanoscale ceramic particle reinforced iron-based composite material. During the sintering process, the mixed powder is pressed by the upper and lower pressure heads to improve the density of the material and the bonding performance of each phase. In order to prevent the iron matrix from reacting with the graphite mold, the inside of the mold is coated with graphite paper, and the cooling method is furnace cooling.
[0061] The invention discloses a micro-nanoscale ceramic particle reinforced high-chromium cast iron-based composite material. The micro-nanoscale ceramic particle reinforced iron-based composite material prepared by ceramic particle surface modification and powder metallurgy provides a new idea for the safe and reliable application of advanced wear-resistant materials; chemical plating enables a layer of NiMo metal plating to be efficiently deposited on the surface of ZTA ceramic particles, which can improve the bonding strength of the heterogeneous interface of the composite material; powder metallurgy can regulate the distribution of ceramic particles in the iron matrix without being restricted by the size and content of the second phase particles; VC nanoparticles synthesized by in-situ reaction improve the strength and wear resistance of the matrix, and the wear resistance is 5.9 to 8.6 times that of high-chromium cast iron.
[0062] The micro-nanoscale ceramic particle reinforced high-chromium cast iron-based composite material of the present invention can be applied to wear-resistant parts.
[0063] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. The components of the embodiments of the present invention described and shown in the drawings here can usually be arranged and designed in various different configurations. Therefore, the following detailed description of the embodiments of the present invention provided in the drawings is not intended to limit the scope of the claimed invention, but merely represents selected embodiments of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0064] Example 1
[0065] First, 50 μm ZTA ceramic particles were soaked in acetone for 10 h, then rinsed with deionized water, and then acid-washed with 50 ml / L H2SO4 and 100 g / L (NH4)2SO4 solutions at room temperature.
[0066] The acid-washed ZTA ceramic particles were then sensitized in a 10 g / L SnCl2 and 30 ml / L hydrochloric acid solution for 10 min; the ZTA ceramic particles were washed with deionized water until the pH value reached 7, and then activated with a 0.1 g / L PdCl2 and 10 ml / L HCl solution for 10 min, and washed with deionized water until neutral;
[0067] Finally, 10g / L NaH2PO2·H2O was used to remove excess Pd ions; a magnetic stirrer was used to assist in chemically plating a NiMo coating on the surface of the micron ZTA ceramic particles. During the chemical plating process, 200ml of plating solution was used for every 50g of ZTA ceramic particles. The main salt was a mixed solution of 10g / L NiSO4·6H2O and 1g / L Na2MoO4·2H2O, 15g / L NaH2PO2·H2O was used as a reducing agent, and the complexing agent was 10g / L CH3COONa. Ammonia water was used to adjust the pH value to 9, and the plating temperature was maintained at 60°C by water bath heating. In order to ensure the concentration and pH of the main salt in the plating solution, the plating solution was replaced every 60 minutes.
[0068] 10wt.% ZTA ceramic particles coated with NiMo coating, 1mL / g alcohol, 1wt.% V powder and high chromium cast iron powder were ball-milled in a high-energy ball mill. The ball milling jar and grinding balls were made of stainless steel. The ball-to-material ratio was 5:1. The ball milling time was 5h and the rotation speed was 100rpm. After ball milling, the mixed powder was dehydrated in a vacuum drying oven and sieved.
[0069] Micro-nanoscale ceramic particle reinforced iron-based composites were prepared by spark plasma sintering technology. The mixed powder was injected into a Φ40×120mm graphite mold. The upper and lower pressure heads were 30MPa during the sintering process. The sintering temperature was 900℃, the heating rate from room temperature to 600℃ was 100℃ / min, the heating rate from 600℃ to the sintering temperature was 50℃ / min, the holding time was 10min, and the vacuum degree was 2×10 -6 Pa, the power supply voltage is 300V, the DC voltage is 3V, the dispersed V powder reacts in situ with the carbon in the matrix to generate VC ceramic particles, which are cooled in the furnace to obtain micro-nanoscale ceramic reinforced iron-based composite wear-resistant parts, whose wear resistance is 5.9 times that of high chromium cast iron.
[0070] See also Figure 1 The cake-shaped material with a diameter of 44 mm is a ZTA ceramic particle reinforced iron-based composite material prepared by discharge plasma technology. The brown irregular particles are ZTA ceramic particles, which are evenly distributed, and the gray matrix is high-chromium cast iron. During the wear process, the large-sized ZTA ceramic particles can effectively resist the wear and tear, thereby protecting the matrix, thus obtaining good wear resistance.
[0071] See also Figure 2, the interface morphology between ZTA ceramic particles and high chromium cast iron in the composite material is given, with ZTA ceramic on the left and high chromium cast iron on the right. It can be seen that the interface is well bonded without obvious defects, which improves the mechanical properties of the composite material and thus extends its service life.
[0072] Example 2
[0073] First, 100 μm ZTA ceramic particles were soaked in acetone for 12 h, then rinsed with deionized water, and then acid-washed with 100 ml / L H2SO4 and 150 g / L (NH4)2SO4 solutions at room temperature;
[0074] The acid-washed ZTA ceramic particles were then sensitized in a 20 g / L SnCl2 and 40 ml / L hydrochloric acid solution for 15 min. The ZTA ceramic particles were washed with deionized water until the pH value was close to 7, and then activated with a 0.2 g / L PdCl2 and 15 ml / L HCl solution for 15 min, and washed with deionized water until neutral.
[0075] Finally, 15g / L NaH2PO2·H2O was used to remove excess Pd ions; a magnetic stirrer was used to assist in chemically plating NiMo on the surface of micron ZTA ceramic particles. During the chemical plating process, 200ml of plating solution was used for every 100g of ZTA ceramic particles. The main salt was a mixed solution of 15g / L NiSO4·6H2O and 2g / L Na2MoO4·2H2O, 20g / L NaH2PO2·H2O as a reducing agent, and 15g / L CH3COONa as a complexing agent. Ammonia water was used to adjust the pH value to 8, and the plating temperature was maintained at 65°C by water bath heating. In order to ensure the concentration and pH of the main salt in the plating solution, the plating solution was replaced every 80 minutes.
[0076] 15wt.% ZTA ceramic particles coated with NiMo coating, 2mL / g alcohol, 2wt.% V powder and high chromium cast iron powder were ball-milled in a high-energy ball mill. The ball milling jar and grinding balls were made of stainless steel. The ball-to-material ratio was 6:1. The ball milling time was 6h and the rotation speed was 150rpm. After ball milling, the mixed powder was dehydrated in a vacuum drying oven and sieved.
[0077] Micro-nanoscale ceramic particle reinforced iron-based composites were prepared by spark plasma sintering technology. The mixed powder was injected into a Φ40×120mm graphite mold. During the sintering process, the upper and lower pressure heads had a pressure of 35MPa, the sintering temperature was 1000℃, the heating rate from room temperature to 600℃ was 100℃ / min, the heating rate from 600℃ to the sintering temperature was 50℃ / min, the holding time was 15min, and the vacuum degree was 4×10 -6Pa, the power supply voltage is 350V, the DC voltage is 3.5V, the dispersed V powder reacts in situ with the carbon in the matrix to generate VC ceramic particles, which are cooled in the furnace to obtain micro-nanoscale ceramic reinforced iron-based composite wear-resistant parts, whose wear resistance is 7.5 times that of high chromium cast iron.
[0078] Example 3
[0079] First, 150 μm ZTA ceramic particles were soaked in acetone for 15 h, then rinsed with deionized water, and then acid-washed with 100 ml / L H2SO4 and 150 g / L (NH4)2SO4 solutions at room temperature.
[0080] The acid-washed ZTA ceramic particles were then sensitized in a 40 g / L SnCl2 and 70 ml / L hydrochloric acid solution for 25 min. The ZTA ceramic particles were washed with deionized water until the pH value was close to 7, and then activated with a 0.4 g / L PdCl2 and 15 ml / L HCl solution for 25 min, and washed with deionized water until neutral;
[0081] Finally, 25g / L NaH2PO2·H2O was used to remove excess Pd ions. A magnetic stirrer was used to chemically plate NiMo on the surface of micron ZTA ceramic particles. During the chemical plating process, 300ml of plating solution was used for every 100g of ZTA ceramic particles. The main salt was a mixed solution of 18g / L NiSO4·6H2O and 4g / L Na2MoO4·2H2O, 20g / L NaH2PO2·H2O as a reducing agent, and 18g / L CH3COONa as a complexing agent. Ammonia water was used to adjust the pH value to 10, and the plating temperature was maintained at 75°C by water bath heating. In order to ensure the concentration and pH of the main salt in the plating solution, the plating solution was replaced every 100min.
[0082] 25wt.% ZTA ceramic particles coated with NiMo coating, 2mL / g alcohol, 4wt.% V powder and high chromium cast iron powder were ball-milled in a high-energy ball mill. The ball milling jar and grinding balls were made of stainless steel. The ball-to-material ratio was 8:1. The ball milling time was 9h and the rotation speed was 200rpm. After ball milling, the mixed powder was dehydrated in a vacuum drying oven and sieved.
[0083] Micro-nanoscale ceramic particle reinforced iron-based composites were prepared by spark plasma sintering technology. The mixed powder was injected into a Φ40×120mm graphite mold. During the sintering process, the upper and lower pressure heads were 38MPa, the sintering temperature was 1100℃, the heating rate from room temperature to 600℃ was 100℃ / min, the heating rate from 600℃ to sintering temperature was 50℃ / min, the holding time was 20min, and the vacuum degree was 6×10 -6Pa, the power supply voltage is 450V, the DC voltage is 3.8V, the dispersed V powder reacts in situ with the carbon in the matrix to generate VC ceramic particles, which are cooled in the furnace to obtain micro-nanoscale ceramic reinforced iron-based composite wear-resistant parts, whose wear resistance is 8.6 times that of high chromium cast iron.
[0084] Example 4
[0085] First, 200 μm ZTA ceramic particles were soaked in acetone for 15 h, then rinsed with deionized water, and then acid-washed with 150 ml / L H2SO4 and 200 g / L (NH4)2SO4 solutions at room temperature.
[0086] The acid-washed ZTA ceramic particles were then sensitized in a 50 g / L SnCl2 and 80 ml / L hydrochloric acid solution for 30 min. The ZTA ceramic particles were washed with deionized water until the pH value was close to 7, and then activated with a 0.5 g / L PdCl2 and 20 ml / L HCl solution for 30 min, and washed with deionized water until neutral.
[0087] Finally, 30 g / L NaH2PO2·H2O was used to remove excess Pd ions. A magnetic stirrer was used to assist in chemically plating NiMo on the surface of micron ZTA ceramic particles. During the chemical plating process, 300 ml of plating solution was used for every 100 g of ZTA ceramic particles. The main salt was a mixed solution of 20 g / L NiSO4·6H2O and 5 g / L Na2MoO4·2H2O, 25 g / L NaH2PO2·H2O as a reducing agent, and 20 g / L CH3COONa as a complexing agent. Ammonia water was used to adjust the pH value to 11, and the plating temperature was maintained at 80°C by water bath heating. In order to ensure the concentration and pH of the main salt in the plating solution, the plating solution was replaced every 120 minutes.
[0088] 30wt.% ZTA ceramic particles coated with NiMo coating, 3mL / g alcohol, 5wt.% V powder and high chromium cast iron powder were ball-milled in a high-energy ball mill. The ball milling jar and grinding balls were made of stainless steel. The ball-to-material ratio was 10:1. The ball milling time was 10h and the rotation speed was 300rpm. After ball milling, the mixed powder was dehydrated in a vacuum drying oven and sieved.
[0089] Micro-nanoscale ceramic particle reinforced iron-based composites were prepared by spark plasma sintering technology. The mixed powder was injected into a Φ40×120mm graphite mold. During the sintering process, the upper and lower pressure heads had a pressure of 40MPa, the sintering temperature was 1200℃, the heating rate from room temperature to 600℃ was 100℃ / min, the heating rate from 600℃ to the sintering temperature was 50℃ / min, the holding time was 20min, and the vacuum degree was 8×10 -6Pa, the power supply voltage is 300V, the DC voltage is 4V, the dispersed V powder reacts in situ with the carbon in the matrix to generate VC ceramic particles, which are cooled in the furnace to obtain micro-nanoscale ceramic reinforced iron-based composite wear-resistant parts, whose wear resistance is 7.3 times that of high chromium cast iron.
[0090] In summary, the present invention provides a micro-nanoscale ceramic particle reinforced high-chromium cast iron-based composite material and its preparation method and application. The NiMo coating is deposited on the surface of the ZTA ceramic particles by a chemical deposition method, and then the ZTA ceramic particles are mixed with V powder, high-chromium cast iron powder and alcohol in a stainless steel ball mill to make them evenly mixed, and then the micro-nanoscale ZTA+VC reinforced high-chromium cast iron-based composite material is obtained by spark plasma sintering technology, which significantly improves the wear resistance. This is mainly because the high-hardness ZTA ceramic particles can resist wear, and at the same time, the in-situ generated nanoscale VC ceramic particles further improve the hardness of the matrix, reducing the hardness difference between the ZTA ceramic particles and the metal matrix.
[0091] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a micro-nanoscale ceramic particle reinforced high chromium cast iron-based composite material, characterized in that: The following steps are involved: The micron ZTA ceramic particles were pickled, sensitized and activated by SnCl2 and PdCl2 respectively. A continuous and dense NiMo metal coating is deposited on the surface of ZTA ceramic particles to obtain NiMo@ZTA; The NiMo@ZTA, V powder, high chromium cast iron powder and alcohol are ball-milled and mixed, so that the V powder and high chromium cast iron powder are evenly coated on the surface of ZTA, and then dried, crushed and sieved in sequence; Under pressure, micro-nanoscale ceramic particle reinforced high chromium cast iron matrix composites were prepared by spark plasma sintering technology.
2. The method for preparing the micro-nanoscale ceramic particle reinforced high chromium cast iron based composite material according to claim 1, characterized in that: The specific pickling treatment is: The ZTA ceramic particles of 50-200 μm were soaked in acetone for 10-15 h, then rinsed with deionized water, and then acid-washed with a mixed solution of 50-150 ml / L H2SO4 and 100-200 g / L (NH4)2SO4 at room temperature; The specific sensitization treatment is: The pickled ZTA ceramic particles are sensitized in a 10-50 g / L SnCl2 and 30-80 ml / L hydrochloric acid solution for 10-30 min; The activation treatment is as follows: The ZTA ceramic particles were rinsed with deionized water until the pH value was 7, and then activated by 0.1-0.5 g / L PdCl2 and 10-20 ml / L HCl solution for 10-30 min.
3. The method for preparing the micro-nanoscale ceramic particle reinforced high chromium cast iron based composite material according to claim 2, characterized in that: After activation, wash with deionized water until neutral; use 10-30 g / L NaH2PO2·H2O to remove excess Pd ions.
4. The method for preparing the micro-nanoscale ceramic particle reinforced high chromium cast iron based composite material according to claim 1, characterized in that: The continuous and dense NiMo metal coating is deposited on the surface of ZTA ceramic particles as follows: Every 50-100g of ZTA ceramic particles are magnetically stirred with 200-300ml of plating solution, the pH value of the plating solution is 9-11, and the plating temperature is maintained at 60-80°C by water bath heating, and the plating solution is replaced every 60-120min.
5. The method for preparing the micro-nanoscale ceramic particle reinforced high chromium cast iron based composite material according to claim 4, characterized in that: The specific plating solution is: The main salt is a mixed solution of 10-20 g / L NiSO4·6H2O and 1-5 g / L Na2MoO4·2H2O, the reducing agent is 15-25 g / L NaH2PO2·H2O, the complexing agent is 10-20 g / L CH3COONa, and the pH value of the plating solution is adjusted with ammonia water.
6. The method for preparing the micro-nanoscale ceramic particle reinforced high chromium cast iron based composite material according to claim 1, characterized in that: The NiMo@ZTA, V powder, high chromium cast iron powder and alcohol are ball-milled and mixed, and then dried, crushed and sieved in sequence. The specific process is as follows: 10-30wt.% ZTA ceramic particles coated with NiMo coating, 1-3mL / g alcohol, 1-5wt.% V powder and high chromium cast iron powder are ball-milled, the ball-ink tank and grinding balls are both made of stainless steel, the ball-to-material ratio is 5:1-10:1, the ball-milling time is 5-10h, the number of revolutions is 100-300rpm, and then vacuum dried and sieved.
7. The method for preparing the micro-nanoscale ceramic particle reinforced high chromium cast iron based composite material according to claim 1, characterized in that: The micro-nanoscale ceramic particle reinforced high chromium cast iron matrix composite material prepared by spark plasma sintering technology is as follows: The sintering temperature was controlled to be 900-1200°C, the heating rate from room temperature to 600°C was 100°C / min, the heating rate from 600°C to sintering temperature was 50°C / min, the holding time was 10-20min, and the vacuum degree was 2-8×10 -6 Pa, the power supply voltage is 300-500V, the DC voltage is 3-4V, the dispersed V powder reacts with the carbon in the matrix in situ to generate VC ceramic particles, which are cooled with the furnace.
8. The method for preparing the micro-nanoscale ceramic particle reinforced high chromium cast iron based composite material according to claim 7, characterized in that: The pressure of the upper and lower pressure heads is 30-40MPa.
9. A micro-nanoscale ceramic particle reinforced high chromium cast iron matrix composite material, characterized in that: Prepared according to the method according to any one of claims 1 to 8.
10. The micro-nanoscale ceramic particle reinforced high chromium cast iron matrix composite material according to claim 9 is applied to wear-resistant parts.
Citation Information
Cited By
High-wear-resistance FeZr-ZTA micro powder coated ZTA ceramic reinforced high-chromium cast iron-based composite material as well as preparation and application thereof
CN119800210A
Carbide ceramic reinforced hot forging die composite material and preparation method thereof
CN122327100A
